Identification of Intestinal Protozoa in Adults in Pasie Nan Tigo Sub-Distric Koto Tangah Padang - Genia Alda Fitria; Nuzulia Irawati; Firdawati Firdawati (Faculty of Medicine, University of Jember, 2022)
Intestinal protozoan infection is one of the leading causes of morbidity and mortality worldwide. However, it is difficult to estimate the true problem of protozoal infections because cases are under-reported. This study aimed to identify intestinal protozoa in healthy adults. This study used a categorical descriptive research design and used a multistage random sampling technique. This research was conducted in Pasie Nan Tigo, Koto Tangah, Padang from July 2020 to December 2021 with a total of 61 samples obtained. Furthermore, the samples were examined using the direct stool examination method and with modified Ziehl-Neelsen staining. The results of this study were obtained, from 61 subjects the most age group was 45-49 years (27.9%), the most gender was female (88.5%), and the incidence of intestinal protozoal infection was 3.3% where only Blastocystis hominis found. The vacuole stage and cyst stage were found to be 50%, respectively. All samples examined were single infection. The conclusion of this study is that Blastocystis hominis infection is still found in healthy adults in Pasie Nan Tigo, Koto Tangah, Padang. Therefore, supportive therapy and measures to prevent infection transmission need to be carried out so that the incidence and morbidity rates can be reduced. Keywords: Intestinal protozoa infections, healthy adult